The impact of COVID-19 pandemic on the Jordanian stock market returns volatility: Evidence from ASE20 - Nahil Ismail Saqfalhait; Omar Mohammad Alzoubi (Economies, 2024)
This research examines the impact of the COVID-19 pandemic on the volatility behavior of Amman Stock Exchange (ASE) returns using ARMA-GARCH-type models for three sub-periods: pre-COVID-19, during COVID-19, and post-COVID-19. The research finds that volatility persistence is significant across all periods, with the pandemic period showing the highest impact of shocks. Bad news has no statistically significant impact on volatility in the pre-COVID-19 period or during the pandemic, while in the post-pandemic period, good news significantly influences volatility. Additionally, there exist notable changes in the autocorrelation and the shock structure of the AR and MA components. Considering these alterations in the asymmetric effects, the AR and MA components suggest significant shifts in market dynamics, investor sentiments, and economic policies in response to pandemic experiences.
Keywords: 330; Amman Stock Exchange; ARCH-type model; COVID-19 pandemic; Jordan; stock returns volatility